PENATALAKSANAAN FISIOTERAPI PADA KASUS CARPAL TUNNEL SYNDROME DI KLINIK FISIOTERAPI SURABAYA: CASE REPORT - Isnani Taqina Iqomi; Agus Widodo; Yasin Galih Ardi (Bajang Institute, 2023)
Background: Carpal Tunnel Syndrome is a neuropathic pressure on the median nerve in the carpal tunnel at the wrist, precisely under the flexor retinaculum. Sensory and motor disturbances occur in the palm, phalanges I, II, III and medial phalange IV. Objective: To know the implementation of physiotherapy to reduce pain, tingling and numbness in cases of Left Carpal Tunnel Syndrome with Ultrasound, TENS and Nerve Gliding Exercise modalities. Methods: The study used the Case Report method conducted at the Surabaya Physiotherapy Clinic in a 55-year-old female patient diagnosed with Carpal Tunnel Syndrome Sinistra physiotherapy with complaints of pain in the left wrist that radiated to the 3rd and 4th fingers. The patient was given intervention in the form of Ultrasound, TENS, and Nerve Gliding Exercise which is carried out 1 week 2 times. Results: Physiotherapy modalities in the form of Ultrasound, TENS, and Nerve Gliding Exercise are able to reduce pain, numbness and numbness, increase joint scope and can restore functional activity. Conclusion: Based on this study using Case Reports, it shows that physiotherapy management using the Ultrasound, TENS, and Nerve Gliding Exercise methods in cases of Carpal Tunnel Syndrome Sinistra as a whole resulted in an increase.